Patient involvement in selection of immunosuppressive regimen following transplantation - Popoola J; Greene H; Kyegombe M; MacPhee IA (Patient Preference and Adherence, 2014)
Joyce Popoola,1,3 Helen Greene,2 Margaret Kyegombe,2 Iain A MacPhee1,3 1Department of Nephrology and Transplantation, 2Department of Pharmacy, St George’s Healthcare NHS Trust, 3St George’s University of London, London, UK Abstract: Transplantation has made a considerable difference to the lives of many patients. However, feedback from patients indicates that although having a transplant is a hugely positive experience, having to take medications indefinitely is one of the biggest challenges. An ideal scenario would be no medications following a transplant. A compromise would be a minimal number of medications, with minimal restrictions and as simple a regimen as possible. Although there is considerable research going into fine-tuning the management of the immune response to a transplant, to date there is no universal regimen that enables patients to remain free of immunosuppressant medications, making adherence paramount to maintain long-term allograft survival. This paper reviews the available immunosuppressant regimens and factors influencing choice from both the clinician’s and the patient’s perspective. Factors influencing the decision-making process, such as quality of life for patients, their satisfaction, acceptability, and adherence uptake are reviewed. We conclude with a further assessment of patient choice as a factor in regimen selection, its impact on adherence, and its implications. Keywords: adherence, transplant, allograft, immunosuppressants, patient involvement, satisfaction, decision-making